Development of a Dynamic Frequency Hopping Code System for Optical Code Division Multiple Access Communications - Ahmad Hamarsheh, Mohammad Mahmoud Naji (2006)
In this work, a novel method of optical code division multiple access (OCDMA) communication system is proposed. This method is based on a code changes dynamically as a function of time and frequency. Thus, the system is referred to as dynamic frequency hopping OCDMA (DFH-OCDMA). The fundamental principles are defined and described with implementation solutions for DFH-OCDMA system. DFH-OCMDA system implementation based on tunable optical filter is found to be an effective solution. Tunable optical filter is found to be able to provide a simple, programmable, and effective solution for the encoding and decoding functions. Only one filter at the encoder and one more at the receiver are required to implement the proposed coding scheme. Special simple codes based on orthogonal sinusoidal functions are also proposed for DFH-OCDMA system. These codes are generated and used to control the tunable optical filters. The effectiveness of the new system with the proposed special codes has been verified and demonstrated using theoretical analysis and computer simulations. Theoretical analysis has been done using 4 MATLAB and MathCAD softwares, while Optisystem 3.0 is used for the computer simulations. A clipping scheme at the receiver is also proposed to enhance the performance of the system and reduce the multiple access interference. The performance results of DFH-OCMDA system shows that the effect of all types of noise, specifically, multiple access interference, phase induced intensity noise, and shot noise have been reduced compared to other OCDMA systems. Thus, the signal to noise ratio and bit error rate performance parameters are improved. For example, at an error rate of 10−¹¹, DFH-OCDMA can accommodate up to 80 users, whereas for other systems, the maximum simultaneous users are 32 for spectral amplitude coding system using Hadamard code, 52 for spectral amplitude coding system using modified quadratic congruence code, 58 for spectral amplitude coding system using modified frequency hopping code, and 24 for fast frequency hopping system. The BER of the DFH-OCDMA system is increasing at a slower rate than that of the other systems, which indicates that there is a significant improvement in performance at large number of users. Indeed it is shown that the BER for DFH-OCDMA is better than any other system at any number of users of more than 50. However, for less than 50 active users, spectral amplitude coding systems gives BER better than that of DFH-OCDMA system. It should be noted that for this range of users, the error rate is too small (less than 10−14).